3-Dimensional alignment of micro components using liquid droplets - Overton, James (2017)
This thesis presents an improved understanding of how liquid surface tension controls component alignment with a focus on factors associated with fabrication quality; offering insight into the impact of adopting the novel additive manufacturing route, and to provide means for designers and engineers, who are not intimately familiar with the dynamics of liquid alignment, to incorporate such features into their work. The work is supported by several novel models and methods created during the PhD project.